Enhancing attachment-based aspects of PCIT for young children with a history of maltreatment - Belanger, Kristine; Gennis, Hannah; Ottenbreit, Nicole; Racine, Nicole (Frontiers in Psychology, 2023)
Disruptive behavior difficulties, such as aggression, non-compliance, and emotional outbursts, are common among children exposed to maltreatment. Parent–Child Interaction Therapy (PCIT) is an effective parenting intervention for addressing child behavior difficulties, however, treatment retention and engagement among parents remain a concern in the clinical setting. This paper describes how the delivery of an intervention that teaches attachment theory concepts (Circle of Security-Parenting, COS-P) prior to PCIT can increase engagement and retention among parents of maltreated children and inform new coaching practices. A detailed description of how to extend and integrate COS-P concepts with PCIT for maltreated families using specific strategies is provided. Recommendations, limitations, and next steps for research are presented.